Lion Hunt: a royal tomb-effigy at Arbroath Abbey - Gimson, G S (Proceedings of the Society of Antiquaries of Scotland, 1996)
Reports the results of research into a fourteenth-century marble effigy's subject matter – thought here to be King William the Lion (d. 1214).